Outer Image of University in the Role of Employer as the Base of Segmentation of Young Potential Employees - Baruk Agnieszka Izabela; Goliszek Anna (Marketing of Scientific and Research Organizations, 2017)
In the article problems of outer image of university as employer are presented. In the theoretical part the gap of knowledge in this scope is identified. It must be underlined that employer image is analysed relatively more seldom than product image or offeror image. It is presented rather in the case of enterprises not in the case of universities. The lack of publications and researches is especially visible in the relation to the perceiving of university in the role of employer by participants of outer labour market. That’s why in the empirical part of this article prepared on the base of the results of field questionnaire research conducted among young potential employees the connotations with university as employer are identified. Applying the method of factor analysis allows to group these connotations. These groups may be treated as the segments of respondents. There are 6 such segments which are very different. Only 2 of them involve respondents declaring positive opinions about universities in the role of employer. The participants of the others segments have rather or completely bad opinions in this matter. It is especially visible in the case of the first segment. On this base the hypothesis H1 can be rejected but H2 shouldn’t be rejected. Respondents perceive university rather in the negative light. It is very important advice for each university because its negative image in the role of employer influences on its general image.